Analisis Sistem Informasi Manajemen Dalam Meningkatkan Kinerja Karyawan PT. Astra Motor Honda Cabang Tongan Malang - DATIN NADLIROH, INDAH; MUDJI, MUDJI (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
PT. Astra Motor Honda is the company where the author conducted research. Currently, the employee performance management system is still done manually, causing a buildup of paper, limited data, and data inequalities.   The type of research used in the research is research with a quantitative descriptive approach. The system development method that the author uses in creating this employee performance information system is to provide a new design for the current information system flow. The result achieved is a management information system, which displays images or charts showing the sequence and relationship between processes along with instructions that display employee value data, creating employee schedules, and financial reports. The management information system that has been developed is expected to simplify and speed up the process of managing the required data and information.